Counter-History of the Present : Untimely Interrogations into Globalization, Technology, Democracy - Rockhill, Gabriel (Book collections on Project MUSE., 2017)
Gabriel Rockhill examines the widespread understanding that we are living in an era of globalization that is bound by economic and technological networks and an unquestionable faith in democracy, replacing it with a counter-history that accounts for the diversity of lived experience and offers new ways to imagine the future.